Care disruptions among the homebound during the COVID‐19 pandemic: An analysis of the role of dementia. Issue 12 (23rd August 2022) - Reckrey, Jennifer M.; Kim, Patricia S.; Zhao, Duzhi; Zhang, Meng; Xu, Emily; Franzosa, Emily; Ornstein, Katherine A.
Abstract: Introduction: Seriously ill people with dementia living at home may be particularly vulnerable to disruptions in their care during times of crisis. The study sought to describe care experiences of those receiving home‐based primary care in New York City during the COVID‐19 pandemic and compare the experiences of people with and without dementia. Methods: We conducted a retrospective review of all electronic medical record notes between March 1, 2020 and December 30, 2020 among a sample of home‐based primary care recipients ( n  = 228), including all deaths that occurred in the spring of 2020. Drawing from administrative records and using an abstraction tool that included both structured (e.g., documented COVID‐19 exposure) and unstructured (e.g., text passage describing caregiver burden) data, we identified salient COVID‐19 related care experiences and identified and categorized major disruptions in care. Results: Both people with and without dementia experienced significant disruptions of paid caregiving, family caregiving, and home‐based services during the COVID‐19 pandemic. While the paid caregivers of people with dementia reported more burden to the home‐based primary care team as compared to people without dementia, we found little evidence of differences in quantity or type of COVID‐19 related disruptions relative to dementia status. Discussion: While those with dementia have distinct care needs, our findings emphasize the way that dementia may be one piece of a larger clinical picture of serious illness. In order to support all patients with high care needs in crisis, we need to understand the interdependence of clinical care, long‐term care, and family caregiving support for older adults and view dementia within the larger context of serious illness and care need.